Pengembangan Modul Bilingual Bergambar dengan Pendekatan Realistic Mathematics Education (RME) pada Materi Himpunan - Nurfithriyya, Aida; Kesuma, Guntur Cahaya; M, Rosida Rakhmawati (Universitas Islam Negeri Raden Intan Lampung, 2020)
Abstract: The purpose of this reaserch is to develop teaching materials consisting of pictorial bilingual modules using Realistic Mathematics Education (RME) on set material and to research the effectiveness of the product being developed. The research used in this research is Research and Development using ADDIE models consisting of motion sickness Analysis, Design, Development, Implementation and Evaluation. This study was declared valid and feasible to be used as teaching material for mathematics learning by 3 material experts who obtained an average score of 3,72 in the